Practices Related to Pregnancy And Child Birth: A Cross Sectional Study Among Women of Ahmedabad District - Yagnavalkya K Jani; Aparajita A Shukla; D V Bala (Medsci Publications, 2013)
Purpose: Improving maternal health is one of the UN Millennium Development Goals. Proper ante-natal visits and professional delivery care not only reduces maternal mortality, but also improves maternal and newborn health. So this study was carried out to assess the practices related to pregnancy and child birth among women of Ahmedabad district and study socio-economic and demographic determinants of use of maternal services. Methodology: A community based cross-sectional study was carried out in urban poor and rural women of Ahmedabad. Study variables included socio-demography, ANC, INC & PNC using the RCH-2 & WHO guidelines. Total 345 mothers of children of 0-36 months were selected by purposive sampling and interviewed after verbal consent. Results: Mean age of mothers was 25.4± 4.18 years. Literacy rate was 78%. Ante-natal registration was 92.8%, but early registration was only 51.6% and through anganwadis only 47.5%. Except for TT, Early registration, IFA and ANC were highly unsatisfactory. Role of education was established as higher education level correlated with better ANC practices (p=0.03). Multiparous women had better ANC practice (p=0.02). Proportion of home delivery was 7%. Proportion of LBW babies was more in women with less than three ante-natal visits (p<0.0001). Conclusion: Present study shows that education has positive effect on practice of ANC, INC and PNC. Awareness about ante-natal visits, avoidance of pre-lacteal feed and strengthening of anganwadis for better pregnancy outcome should be promoted.